Pelatihan Pengembangan Bahan Ajar Komik Berbantuan AI dan Dampaknya Terhadap Hasil Belajar - Aeng Muhidin; Heri Kurnia; Shinta Doriza; Abd. Chaidir Marasabessy (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
Elementary school teachers face challenges in developing teaching materials that are engaging and adaptive to students' learning needs, while the use of generative Artificial Intelligence (AI) for this purpose remains limited, particularly in the ability to compose structured prompts. This community service activity focused on improving the competence of teachers at SDN Rawajati 06 Pagi in developing AI-assisted comic-based teaching materials and measuring its impact on student learning outcomes. The activity aimed to improve teachers' understanding of prompt engineering principles for producing contextual instructional comics and to evaluate its effectiveness on student learning outcomes. The methods used included a needs analysis through a pre-training questionnaire, material presentation and demonstration, hands-on practice in composing AI prompts, a post-training questionnaire, and a classroom trial of the resulting comics evaluated through a pretest-posttest design involving 21 students. The results showed significant improvement in teacher competence: the percentage of teachers able to compose structured comic prompts increased from 0% to 55.6%, the use of AI to create comics increased from 11.1% to 57.1%, and all participants (100%) expressed satisfaction with the training. At the student level, the average learning outcome score increased from 7.10 to 8.43, with an N-Gain of 0.50 (moderate category) and a paired t-test showing a significant difference (p < .001). This activity demonstrates that training in AI prompt composition for comic-based teaching materials effectively improves teachers' digital competence and positively impacts student learning outcomes.